The Truth in Art - Jackūnas, Žibartas (Problemos, 1983)
The problem of gnoseological status of art works is considered. Different approaches to the problem of interrelation between art and logical judgement which plays the part of point of departure in solving the problem are discussed. The views on “art truth” as a non-gnoseological category on the concept of “art judgement”, on the denial of truth in art based on the refusal to recognize the status of logical judgements for works of art, are subjected to a critical estimation. An attempt is made to solve the problem of truth in art by comprehending the similarity between a work of art and non-artistic reality.